Association of caregiver attitudes with adolescent HPV vaccination in 13 southern US states. (August 2022) - Vasudevan, Lavanya; Ostermann, Jan; Wang, Yunfei; Harrison, Sayward E.; Yelverton, Valerie; Fish, Laura J.; Williams, Charnetta; Walter, Emmanuel B.
Highlights: Low adolescent HPV vaccination in the US South is linked to caregiver attitudes. Adapted measures of general and vaccine-specific attitudes predict HPV vaccination. Caregivers' general concerns are with vaccine ingredients, side effects, and number. Perceived inadequacy of research and vaccine effectiveness linked to non-vaccination. HPV vaccine-specific messaging may be needed to change caregiver attitudes. Abstract: Background and objectives: HPV vaccination coverage is lower than that of other adolescent vaccines in the southern US. This study sought to characterize caregiver attitudes associated with adolescent HPV vaccination in the southern US and to inform interventions to promote HPV vaccination. Methods: From December 2019 – January 2020, caregivers of adolescents (ages 9–17 years) living in thirteen southern US states were recruited from a nationally-representative online survey panel. Caregivers (N = 1, 105) completed a cross-sectional survey that assessed general adolescent vaccine attitudes as well as those associated with the HPV vaccine and HPV vaccination decision-making. The primary study outcome was adolescents' receipt of at least one dose of the HPV vaccine. Results: Caregivers with vaccinated adolescents had greater positive attitudes towards adolescent vaccines compared to caregivers of unvaccinated adolescents. Top three areas of concern among caregivers were related to vaccine ingredients, perceptions that adolescents receive too many vaccines, and worry about vaccine side effects. In multivariable regression models, positive attitudes towards the HPV vaccine and HPV vaccination decision-making strongly associated with HPV vaccination in addition to general adolescent vaccination attitudes. Caregivers' reported discomfort with discussing the topic of sex was predictive of lower vaccination uptake for older adolescents. Conclusions: Public health messaging in the southern US should be tailored to reduce concerns about vaccine safety and to communicate the importance of timely HPV vaccination. Campaigns that deliver information specific to the HPV vaccine and to support vaccination decision-making may be more effective than those delivering only general adolescent vaccination information at promoting on-time HPV vaccination.